Cloudiness in relation to moisture and convergence - BANERJI, R. C.; UPADHYAY, D. S.; MISRA , D. K.; ARYA, H. C. (MAUSAM, 1973)
The day to day variation of moisture content and lover level convergence pattern over New Delhi have been examined with a view to, find a correlation between these two meteorological parameters and different cloud types and amounts. An empirical relationship has also been established. This study reveals the mean values of moisture content in a vertical air column and lower level convergence, most favourable for the development of period the different cloud types and low cloud amounts along with their confidence bands.